Wild-Type Measles Virus is Intrinsically Dual-Tropic - Takeda, Makoto; Tahara, Maino; Nagata, Noriyo; Seki, Fumio (Frontiers in Microbiology, 2012)
Measles is a highly contagious disease that causes temporary and severe immunosuppression in patients. Signaling lymphocyte activation molecule (SLAM) expressed on cells of the immune system functions as a receptor for measles virus (MV). In addition to SLAM, vaccine strains of MV also use a ubiquitously expressed complement regulatory protein, CD46, as a receptor, whereas wild-type (wt) MV strains do not use this receptor. However, recent studies have indicated that SLAM is not the sole receptor for wt MV strains. These strains have an intrinsic ability to enter both immune and epithelial cells using distinct receptor binding sites in their hemagglutinin (H) protein. Recently, a clear answer was obtained through the identification of an epithelial MV receptor, nectin4, expressed at adherens junctions, thereby greatly improving our knowledge of MV receptors. It is now clear that MV specifically targets two cell types, immune cells and epithelial cells, using SLAM and nectin4, respectively. MV loses the ability to use either SLAM or nectin4 when it possesses specific mutations in the H protein. However, nectin4-blind MV still infects SLAM-positive immune cells efficiently (SLAM-tropic), and conversely, SLAM-blind MV infects nectin4-positive epithelial cells efficiently (nectin4-tropic). In this regard, MV is intrinsically dual-tropic to immune cells and epithelial cells. Although many aspects and molecular mechanisms underlying immunosuppressive effects and a highly contagious nature of MV still remain to be elucidated, analyses of physiological functions of these two receptors would provide deep insights into MV pathogenesis.